Dificuldades de aprendizagem no processo de aquisição da leitura e escrita na EMEF "O Mundo da Criança" - ALVES, Maria dos Reis da Silva (2019)
This work deals with Learning difficulties in the process of acquisition of reading and writing in EMEF "The World of the Child", in the urban area of the municipality of Novo Repartimento-PA. The objective of this research is to analyze cases of learning difficulties in the process of acquisition of reading and writing of the students of the Municipal School of Elementary Education "The World of the Child" and how the teachers perceive through bimonthly soundings to observe this process at the end of the 3rd year. The methodology was divided in two moments: the theoretical referential survey, classroom observation, questionnaire application to two teachers and verification of reading and writing of third year students, where after answering question number one could be understood the different levels of each of the children selected by the teachers through a lottery. The data revealed that students have difficulties in reading and writing, some of them being at the pre-syllabic level, and that teachers have difficulties in literacy mainly because they do not have didactic materials and lack of creative methodologies in the literacy process, but always remembering that each child has its own development.